Copper-based brazing filler metal for CBN tool brazing and preparation method and application of copper-based brazing filler metal
By refining and decentralizing the CBN tools with copper -based ingredients, the coordinated effects of MN, CR, and TI elements are regulated, and the problem of insufficient performance of copper -based ingredients under high temperature and heavy load conditions has been solved. Power, hardness and abrasion resistance extend the service life of the tool.
Patent Information
- Application Number
- CN202411753722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The copper-based solder material for existing CBN tools is insufficient in performance under high temperature and heavy load conditions, which is easy to soften and lead to abrasive particles falling off, and the presence of inclusions leads to cracking at the welding site, affecting the service life of the tool.
By refining the copper alloy melt, the inclusion content is reduced and the alloy purity is improved; the alloy powder is treated with a dispersant to improve its fluidity and dispersion; the synergistic effect of Mn, Cr, and Ti elements is controlled to control the melting point of the solder. and wettability.
It significantly improves the high temperature performance and abrasion resistance of copper -based ravioli, enhances the intensity of binding, extends the service life of the tool, and improves the welding effect.
Smart Images

Figure CN119347205A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brazing materials, and in particular to a copper-based brazing filler metal for brazing CBN tools and a preparation method thereof. Background Art
[0002] Cubic boron nitride (CBN) tools have the characteristics of high hardness, good stability, and inert reaction with iron group elements. They are widely used in the grinding of high-speed steel, tool steel, die steel, wear-resistant cast iron and other iron-containing materials and titanium alloy materials. Among them, brazed CBN tools have high bonding strength, no need for dressing, strong abrasive holding force, large chip space, and a service life that is several times that of electroplated CBN tools. The processing time can also be reduced by 1 / 3, and it has gradually become one of the main preparation processes for single-layer CBN tools.
[0003] At present, the brazing filler metals for brazing CBN tools mainly include three series: silver-based active brazing filler metals, copper-based active brazing filler metals, and nickel-based high-temperature brazing filler metals. Although CBN tools made of silver-based active brazing filler metals have been widely used in the processing of iron-based materials or alloys, the low operating temperature, poor high-temperature stability, poor hardness and wear resistance, and high material cost of silver-based brazing filler metals limit their wide application. Nickel-based high-temperature brazing filler metals have too high melting temperatures, are easy to damage the base material, have poor wettability, and poor thermal conductivity, and are also not widely used in the brazing of CBN tools. Copper-based brazing filler metals represented by copper-tin-titanium active brazing filler metals are the most promising alternative brazing fillers for brazing CBN tools. They have the advantages of good thermal conductivity, low cost, good wettability, and good mechanical properties, and have been increasingly widely studied and applied. However, under the conditions of high grinding temperatures and heavy loads, the high-temperature performance of copper-based brazing filler metals is still poor, and they are prone to softening, resulting in the shedding of abrasive particles that affects the service life of the tool, and their strength and wear resistance are insufficient.
[0004] In addition, the current multi-element copper-based brazing alloy powder is rarely treated by refining during the melting and atomization process. The inclusion phase in the alloy powder will continue to the brazing and use process, becoming a stress concentration site, causing cracks at the weld, and affecting the service life of the tool. There are two ways to coat the copper-based brazing filler metal for CBN tools. One is to first coat a layer of colloid on the surface of the substrate, then evenly distribute the copper-based alloy powder on the colloid, and then arrange orderly CBN abrasives, and obtain the CBN tool after vacuum brazing; the other is to make the copper-based alloy powder into solder paste and evenly apply it on the surface of the substrate, and then arrange orderly CBN abrasives, and obtain the CBN tool after vacuum brazing. Regardless of the method, the better the dispersibility of the brazing filler metal, the better the uniformity of the coating, which is conducive to improving the brazing effect. However, the defects such as satellite powder and capped powder generated during the atomization process of the copper-based alloy powder make the powder dispersibility and fluidity poor.
[0005] Therefore, in view of the above-mentioned problems that still exist in copper-based brazing filler metals for CBN tools, it is necessary to develop a new type of copper-based brazing for CBN tools suitable for heavy load and high temperature working conditions. Summary of the invention
[0006] In view of the above-mentioned shortcomings, the present invention provides a copper-based brazing filler metal for CBN tool brazing and its preparation method and application. The present invention effectively reduces the inclusion content by more than 6.0% by refining the copper alloy melt, thereby improving the purity of the alloy. By dispersing the alloy powder, the fluidity of the powder is significantly improved, and the bulk density is increased by more than 10.0%, ensuring that the powder is spread more evenly and densely on the colloid on the surface of the substrate. The copper-based brazing filler metal designed by the present invention controls the melting point of the brazing filler metal between 920 and 960°C by regulating the synergistic effect of Mn, Cr, and Ti elements, ensuring that the use temperature of the CBN tool can reach 500 to 600°C; the main wetting effect of Ti and Cr elements is adopted, and the wettability of the brazing filler metal to the base material is further improved without increasing the brittle phase; the brazing filler metal has higher bonding strength, good hardness and wear resistance, and is suitable for heavy-load and high-temperature grinding scenes.
[0007] In order to achieve the above-mentioned object, the present invention provides a copper-based brazing filler metal for CBN tool brazing, which comprises, by mass percentage, 15.0% to 20.0% manganese, 1.0% to 3.0% nickel, 1.0% to 1.8% chromium, 6.0% to 9.0% titanium, the remainder being copper, and the total amount of impurity elements being less than 0.3%.
[0008] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned copper-based brazing filler metal for CBN tool brazing, comprising the following steps:
[0009] S1. Place metal copper, metal manganese, metal nickel, metal chromium and metal titanium in a vacuum medium frequency induction furnace for smelting. After the raw materials are melted and mixed, add a refining agent for refining to obtain an alloy melt. The amount of the refining agent added is 0.1% to 0.4% of the total mass of the metal raw materials.
[0010] It should be noted that the amount of refining agent added in the present invention is 0.1% to 0.4% of the total mass of the raw materials. For example, 100 kg of raw materials (the sum of copper, manganese, nickel, chromium and titanium) need to be added with 100 g to 400 g of refining agent.
[0011] S2. Using an inert gas to perform vacuum gas atomization treatment on the alloy melt to obtain alloy powder.
[0012] Furthermore, the preparation method further comprises:
[0013] S3. Mixing the alloy powder with a dispersant at 45-60° C. and under vacuum conditions to obtain copper-based alloy powder.
[0014] Furthermore, in step S1, the smelting temperature is 1150°C to 1300°C, and the vacuum degree is ≤40Pa; the refining temperature is 1050°C to 1200°C, and the refining time is 3 to 5 minutes.
[0015] Further, in step S1, the refining agent includes, by mass percentage, 17.0% to 22.0% sodium fluoroborate, 20.0% to 25.0% potassium fluorotitanate, 15.0% to 25.0% cryolite, 15.0% to 20.0% nano-barium carbonate, and 11.0% to 26.0% nano-manganese carbonate.
[0016] It should be noted that, on the basis of the traditional fluorotitanate and fluoroborate refining agents, the present invention adds nano carbonate, barium carbonate, manganese carbonate, and tiny inert bubbles generated by barium carbonate and manganese carbonate during the heating process. Since the partial pressure of the included gas such as hydrogen in the bubble is zero, while the partial pressure of the gas inclusions in the melt is much greater than zero, the partial pressure difference in the bubble is easy to adsorb the non-metallic inclusions in the melt into the inert bubbles, which greatly improves the removal effect of the refining agent on the non-metallic inclusions. The MnO in the decomposition product of manganese carbonate is easy to react with oxygen at high temperature to generate more stable oxides, such as manganese silicate, thereby achieving deoxidation, desiliconization and other effects, and further improving the purity of the melt. In addition, the presence of inert atmosphere (carbon dioxide generated by carbonate decomposition) not only reduces the corrosion of the toxic corrosive gas of boron trifluoride released by the traditional fluorotitanate and fluoroborate refining agents when decomposed at high temperature to the equipment, but also accelerates the rate at which the double salt formed by fluorotitanate and fluoroborate floats to the surface of the melt, reduces the stationary time of the melt, and thus reduces the element burning loss.
[0017] Furthermore, in step S2, the temperature of the vacuum air atomization treatment is 1050-1150°C, the atomization rate is 4-6 kg / min, the spray angle of the atomizer is 35-45°, and the atomization pressure is 4-6 MPa.
[0018] Furthermore, in step S3, the mass percentage of the alloy powder to the dispersant is 50-60:1, the vacuum degree is 80-200 Pa, and the mixing time is 10-20 min.
[0019] Further, in step S3, the dispersant includes, by mass percentage, 90.0% to 97.0% acetone, 0.5% to 1.0% methyl palmitate, 2.0% to 5.0% palmitic acid, and 0.2% to 1.7% dodecanoic acid.
[0020] It should be noted that the copper-based alloy powder is directly spread on the adhesive of the substrate, which puts higher requirements on the dispersion and fluidity of the powder. The copper-based alloy powder has poor morphology, many satellite powders and capped powders, easy moisture absorption and agglomeration, etc., which often cause the alloy powder to be blocked in the duct and unevenly distributed during the powder spreading process. The dispersant used in the present invention is used to treat the alloy powder. First, the alloy powder is coated with methyl palmitate, palmitic acid, and dodecanoic acid to reduce the electrostatic adsorption and oxidation process between the powders. The dispersant is more strongly combined with the adhesive on the surface of the substrate, and its good thermal stability can reduce the shedding of the powder during the brazing process, which is conducive to increasing the climbing height of the solder; second, the acetone in the dispersant will evaporate completely during the dispersion process, and the remaining organic content is less than 0.08%. The trace amount of dispersed substances is easy to remove during the brazing process and will not affect the quality of the weld. Therefore, compared with the commonly used alloy powder dispersant, lubricant or surfactant added in an amount of more than 0.5%, the present invention achieves a better alloy powder dispersion effect with less dispersant.
[0021] Based on the same inventive concept, the present invention also provides the use of the copper-based brazing filler metal for CBN tool brazing or the copper-based brazing filler metal for CBN tool brazing prepared by any of the above preparation methods, and the use comprises the following steps:
[0022] The 80% to 90% alloy powder or copper-based alloy powder and 10% to 20% binder are mixed to obtain a copper-based solder paste, the solder paste is evenly applied on the surface of the substrate, and then orderly CBN abrasives are arranged, and vacuum brazing is performed to obtain a CBN tool;
[0023] Alternatively, the alloy powder or copper-based alloy powder is evenly distributed on the colloid on the surface of the substrate, and then orderly CBN abrasives are arranged thereon, and the CBN tool is obtained after vacuum brazing.
[0024] It should be noted that the alloy powder and copper-based alloy powder are actually copper-based alloy powders, and they are named differently only to distinguish step S3. When the preparation method only contains step S1 and step S2, the alloy powder is bonded with the binder / uniformly distributed on the surface of the substrate; when the preparation method also includes step S3, the copper-based alloy powder is bonded with the binder / uniformly distributed on the surface of the substrate.
[0025] Furthermore, the binder is composed of the following components: 58.0% to 75.0% solvent, 8.0% to 15.0% thickener, 5.0% to 12.0% antioxidant, and 1.0% to 5.0% active agent; wherein the solvent includes butyl octanol and dimethyl sulfoxide; the thickener includes ethyl cellulose and hexyldecanol; the antioxidant is oxalic acid; and the active agent includes palmitic acid and hexadecanoic acid.
[0026] Beneficial effects of the present invention:
[0027] The present invention effectively reduces the inclusion content by more than 6.0% by refining the copper alloy melt, thereby improving the purity of the alloy; by dispersing the alloy powder, the fluidity of the powder is significantly improved, and the bulk density is increased by more than 10.0%, ensuring that the powder is spread more evenly and densely on the colloid on the surface of the substrate. The copper-based solder designed by the present invention controls the melting point of the solder between 920 and 960°C by regulating the synergistic effect of Mn, Cr, and Ti elements, ensuring that the operating temperature of the CBN tool can reach 500 to 600°C; the main wetting effect of Ti and Cr elements is used to further improve the wettability of the solder to the base material without increasing the brittle phase; the solder has higher bonding strength, good hardness and wear resistance, and is suitable for heavy-load and high-temperature grinding scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The particle size distribution of the alloy powder prepared in Example 1 of the present invention;
[0029] Figure 2 This is a scanning electron microscope image of the alloy powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0031] Example 1
[0032] S1. Its chemical composition, by mass percentage, includes: 15.0% Mn, 1.0% Ni, 1.0% Cr, 6.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper. Metal copper, metal manganese, metal nickel, metal chromium, and metal titanium are placed in a vacuum induction furnace. Under the conditions of medium frequency induction (85-100KW, 950-1100HZ) and vacuum degree 20-30Pa, the raw materials are completely melted and stirred for 7 minutes to obtain a mixed alloy melt. At a temperature of 1100-1200°C, 0.1% refining agent is added to the alloy melt and refined for 3 minutes. The refining agent composition is 19.0% sodium fluoroborate, 23.0% potassium fluoroborate, 21.0% cryolite, 17.0% nano barium carbonate, and 20.0% nano manganese carbonate to obtain a refined alloy melt.
[0033] S2. The obtained alloy melt is vacuum gas atomized with high-purity argon (purity ≥99.999%), the spray angle of the atomizer is 35-40°, the atomization gas pressure is 5.5-6MPa, the atomization temperature of the alloy melt is 1100-1150°C, the atomization rate is 5-6kg / min, and the alloy powder is obtained.
[0034] S3. At a temperature of 45-50°C, the alloy powder and the dispersant are mixed to obtain a dispersed copper-based alloy powder. The mass percentage of the alloy powder and the dispersant is 58:1, the vacuum degree is 80-100 Pa, and the mixing time is 20 minutes. The composition and mass percentage of the dispersant include: 95.0% acetone, 0.5% methyl palmitate, 4.0% palmitic acid, and 0.5% dodecanoic acid.
[0035] S4. Distribute the dispersed copper-based alloy powder evenly on the colloid on the surface of the substrate, arrange the CBN abrasive in an orderly manner, and obtain the CBN tool after vacuum brazing.
[0036] Example 2
[0037] The atomization powder making process of Example 2 is the same as that of Example 1, except that: there is no alloy powder dispersion step (S3), but 75.0% solvent, 12.0% thickener, 10.0% antioxidant, and 3.0% activator are mixed to obtain a binder. Using a high-speed disperser, 85.0% alloy powder and 15.0% binder are evenly mixed to obtain a copper-based solder paste. Among them, the mass ratio of butyl octanol: dimethyl sulfoxide in the solvent is 4:1, the mass ratio of ethyl cellulose: hexyl decanol in the thickener is 3:2, and the mass ratio of palmitic acid: hexadecanoic acid hexadecyl in the activator is 7:3. The solder paste is evenly applied to the surface of the substrate, and then orderly CBN abrasives are arranged on it, and the CBN tool is obtained after vacuum brazing.
[0038] The remaining steps are the same as those in Example 1.
[0039] Example 3
[0040] Example 3 is substantially the same as Example 1, except that, by mass percentage, its chemical composition includes: 20.0% Mn, 3.0% Ni, 1.8% Cr, 9.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper. In addition, at a temperature of 1100-1200° C., 0.3% refining agent is added to the alloy melt and refined for 3 minutes, the refining agent composition is 22.0% sodium fluoroborate, 25.0% potassium fluoroborate, 23.0% cryolite, 15.0% nano barium carbonate, and 15.0% nano manganese carbonate, to obtain a refined alloy melt.
[0041] The remaining steps are the same as those in Example 1.
[0042] Example 4
[0043] Example 4 is substantially the same as Example 2, except that 73.0% of solvent, 10.0% of thickener, 12.0% of antioxidant, and 5.0% of active agent are mixed to obtain a binder. 90.0% of alloy powder and 10.0% of binder are uniformly mixed using a high-speed disperser to obtain a copper-based solder paste.
[0044] The remaining steps are the same as those in Example 2.
[0045] Example 5
[0046] Example 5 is basically the same as Example 1, except that the mass percentage of alloy powder to dispersant is 52:1, the vacuum degree is 80-100 Pa, and the mixing time is 20 min. The dispersant composition and its mass percentage include: 94.5% acetone, 1.0% methyl palmitate, 3.0% palmitic acid, and 1.5% dodecanoic acid.
[0047] The remaining steps are the same as those in Example 1.
[0048] Comparative Example 1
[0049] Comparative Example 1 is substantially the same as Example 1, except that Comparative Example 1 does not include a melt refining process.
[0050] The remaining steps are the same as those in Example 1.
[0051] Comparative Example 2
[0052] Comparative Example 2 is substantially the same as Example 1, except that Comparative Example 2 does not include an alloy powder dispersion process.
[0053] The remaining steps are the same as those in Example 1.
[0054] Comparative Example 3
[0055] Comparative Example 3 is substantially the same as Example 2, except that Comparative Example 3 is a commercial copper-tin-titanium alloy powder, and its chemical composition, by mass percentage, includes: 19% Sn, 10.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.
[0056] The remaining steps are the same as those in Example 2.
[0057] Comparative Example 4
[0058] Comparative Example 4 is a commercial copper-tin-titanium active solder paste, and the chemical composition of the copper-tin-titanium solder includes, by mass percentage, 19% Sn, 10.0% Ti, less than 0.3% total impurity elements, and the rest is copper. The solder paste is evenly applied to the surface of the substrate, and then orderly CBN abrasives are arranged on it, and a CBN tool is obtained after vacuum brazing.
[0059] Comparative Example 5
[0060] Comparative Example 5 is a commercial nickel-based solder paste. The chemical composition of the nickel-based solder includes, by mass percentage, 7.0% Cr, 3.0% B, 4.5% Si, 3.0% Fe, the total amount of impurity elements is less than 0.3%, and the rest is nickel. The solder paste is evenly applied to the surface of the substrate, and then orderly CBN abrasives are arranged on it, and a CBN tool is obtained after vacuum brazing.
[0061] Performance testing and result analysis:
[0062] The copper-based alloy powder prepared in Example 1 was tested for particle size and microscopic morphology. The particle size distribution of the copper-based alloy powder is as follows: Figure 1 As shown by Figure 1 It can be seen that the median particle size of the copper-based alloy powder prepared in this embodiment is small and the particle size distribution is relatively concentrated, indicating that the impurity content in the copper-based alloy powder prepared in this application is small. Figure 2 As shown by Figure 2 It can be seen that the copper-based alloy powder prepared in the present application is evenly dispersed, and the loose density of the copper-based alloy powder prepared in the present application is high.
[0063] The inclusion volume fraction of the alloy powders obtained in the examples and comparative examples was tested and calculated. The inclusion volume fraction was calculated as follows:
[0064] Inclusion size is expressed as inclusion equivalent diameter d avg express,
[0065] In the formula, A inclusion is the area of a single inclusion obtained by image analysis software, μm 2 .
[0066] The average volume fraction of inclusions F avgCalculated by the following formula:
[0067]
[0068] In the formula, A field is the area of the metallographic field of view, μm 2 .
[0069] The melting characteristics of the copper-based active brazing alloy powders obtained in some embodiments and comparative examples were tested, and the results are shown in Table 1.
[0070] Table 1 Characteristics of brazing alloy powders of some embodiments and comparative examples
[0071]
[0072] As shown in Table 1, compared with the copper-based alloy powder in the comparative example, the copper-based alloy powder prepared by the present invention has a bulk density of less than 4.8 g / cm 3 , increased to more than 5.4g / cm 3 , an increase of more than 12%; the Hall flow velocity has been significantly reduced, and the lower the Hall flow velocity value, the better the fluidity of the powder. In addition, compared with the alloy powder that has not been refined, the volume fraction of inclusions in the refined alloy powder is reduced to 0.08%, a decrease of more than 27%, and the melt purification effect is obvious. It can be seen from the melting temperatures of the embodiments and comparative examples that compared with commercial copper-tin-titanium solder, the copper-based solder prepared by the present invention has a higher melting temperature, which is beneficial to improving the thermal stability of CBN tools during use. Compared with commercial nickel-based solder, it has a lower melting point and is not easy to cause brazing damage to the parent material.
[0073] The brazing performance of the copper-based active brazing alloy powders obtained in the examples and comparative examples was tested. The results are shown in Table 2.
[0074] Table 2 Comparison of brazing performance of the embodiments and comparative examples
[0075]
[0076] As can be seen from Table 2, compared with the commercial copper-based brazing filler metals in Comparative Examples 3 and 4, the copper-based brazing filler metals prepared by the present invention, under the synergistic effect of Ti and Cr elements, have the same content of active elements, and the brazing filler metal in Example 3 has a smaller wetting angle to the CBN abrasive grains, showing better wettability. After melt purification, brazing dispersion and the synergistic effect of low-content brittle phase, the brazing interface between the brazing filler metal of the present invention and the steel substrate is dense, with fewer impurity points of stress concentration, and thus has higher shear strength. Under the same grinding conditions, the number of grinding feeds before the tool fails is also higher, indicating that the tool has a longer service life.
[0077] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A copper-based brazing filler metal for CBN tool brazing, characterized in that: Calculated by mass percentage, the copper-based solder includes: 15.0% to 20.0% manganese, 1.0% to 3.0% nickel, 1.0% to 1.8% chromium, 6.0% to 9.0% titanium, the balance is copper, and the total amount of impurity elements is less than 0.3%.
2. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 1, characterized in that: The following steps are involved: S1. Place metal copper, metal manganese, metal nickel, metal chromium and metal titanium in a vacuum medium frequency induction furnace for smelting. After the raw materials are melted and mixed, add a refining agent for refining to obtain an alloy melt. The amount of the refining agent added is 0.1% to 0.4% of the total mass of the metal raw materials. S2. Using an inert gas to perform vacuum gas atomization treatment on the alloy melt to obtain alloy powder.
3. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 2, characterized in that: The preparation method further comprises: S3. Mixing the alloy powder with a dispersant at 45-60° C. and under vacuum conditions to obtain copper-based alloy powder.
4. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 2, characterized in that: In step S1, the smelting temperature is 1150°C to 1300°C, and the vacuum degree is ≤40Pa; the refining temperature is 1050°C to 1200°C, and the refining time is 3 to 5 minutes.
5. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 2, characterized in that: In step S1, the refining agent includes, by mass percentage, 17.0% to 22.0% sodium fluoroborate, 20.0% to 25.0% potassium fluorotitanate, 15.0% to 25.0% cryolite, 15.0% to 20.0% nano-barium carbonate, and 11.0% to 26.0% nano-manganese carbonate.
6. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 2, characterized in that: In step S2, the temperature of the vacuum air atomization treatment is 1050-1150°C, the atomization rate is 4-6 kg / min, the spray angle of the atomizer is 35-45°, and the atomization pressure is 4-6 MPa.
7. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 3, characterized in that: In step S3, the mass percentage of the alloy powder to the dispersant is 50-60:1, the vacuum degree is 80-200 Pa, and the mixing time is 10-20 min.
8. The method for preparing the copper-based brazing filler metal for CBN tool brazing according to claim 3, characterized in that: In step S3, the dispersant includes, by mass percentage, 90.0% to 97.0% acetone, 0.5% to 1.0% methyl palmitate, 2.0% to 5.0% palmitic acid, and 0.2% to 1.7% dodecanoic acid.
9. Use of the copper-based brazing filler metal for CBN tool brazing as claimed in claim 1 or the copper-based brazing filler metal for CBN tool brazing prepared by the preparation method according to any one of claims 2 to 8, characterized in that: The application comprises the following steps: The 80.0% to 90.0% alloy powder or copper-based alloy powder and 10.0% to 20.0% binder are mixed to obtain a copper-based solder paste, the solder paste is evenly applied on the surface of the substrate, and then orderly CBN abrasives are arranged, and vacuum brazing is performed to obtain a CBN tool; Alternatively, the alloy powder or copper-based alloy powder is evenly distributed on the colloid on the surface of the substrate, and then orderly CBN abrasives are arranged thereon, and the CBN tool is obtained after vacuum brazing.
10. The use according to claim 9, characterized in that: The binder is composed of the following components in percentage by mass: 58.0% to 75.0% of a solvent, 8.0% to 15.0% of a thickener, 5.0% to 12.0% of an antioxidant, and 1.0% to 5.0% of an active agent; wherein the solvent comprises butyl octanol and dimethyl sulfoxide; the thickener comprises ethyl cellulose and hexyldecanol; the antioxidant is oxalic acid; and the active agent comprises palmitic acid and hexadecanoic acid hexadecyl.
Citation Information
Patent Citations
Brazing active solder for diamond abrasive products
CN109465567A
Mn-containing copper-based brazing filler metal for brazing diamond as well as preparation method and brazing method of Mn-containing copper-based brazing filler metal
CN117840637A
Brazing material and brazed product manufacted therewith
CN1514758A
Hard solder on the basis of copper@ for soldering porous sinter steels
DE4404406A1
Metal-ceramic brazing material paste and electronic part
JP1990006096A
Cited By
Preparation method of molybdenum disulfide coating for steel lead screw
CN120425338A